Carbide-based nano composite film as well as preparation method and application thereof
By alternately stacking CrMnFeCoNi alloy nanolayers in the carbide coating, a carbide-based nanocomposite film is constructed, which solves the problem of prone to cracks in harsh environments, and achieves a comprehensive improvement of high hardness, fracture toughness and wear resistance.
Patent Information
- Application Number
- CN202411448349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-17
AI Technical Summary
Carbide coatings are prone to cracks and failure in demanding service environments, limiting their application in engineering fields.
Carbide-based nanocomposite film was constructed using alternately laminated carbide nanolayers and CrMnFeCoNi alloy nanolayers, and the film was prepared by magnetron sputtering technology.
The high hardness, high fracture toughness and high wear resistance of the carbide-based nanocomposite film are achieved, which significantly reduces the crack failure of the material under service conditions and extends the service life of the material and equipment.
Smart Images

Figure CN119530708A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of protective materials, and specifically relates to a carbide-based nanocomposite film and a preparation method and application thereof. Background Art
[0002] Carbide coatings have the characteristics of high hardness, high wear resistance and corrosion resistance, and are widely used in mechanical processing, cutting, welding and wear protection. For example, on the blades of gas turbines, carbide coatings can effectively enhance the wear resistance of the surface; on the surface of mechanical parts, carbide coatings can effectively extend the service life of parts.
[0003] However, due to the low fracture toughness of carbide coatings, they are prone to cracking and failure in harsh service environments. For example, on the surface of tools or bearings, long-term mechanical loads can lead to the generation and expansion of microcracks, thus limiting the application of carbide coatings in the engineering field. Summary of the invention
[0004] The purpose of the present invention is to provide a carbide-based nanocomposite film and a preparation method and application thereof. The carbide-based nanocomposite film provided by the present invention has high hardness, high wear resistance and high fracture toughness.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a carbide-based nanocomposite film, comprising alternately stacked carbide nanolayers and CrMnFeCoNi alloy nanolayers; the molar ratio of Cr, Mn, Fe, Co and Ni in the CrMnFeCoNi alloy nanolayers is 18-22:18-22:18-22:18-22:18-22.
[0007] Preferably, the carbide nanolayer is a WC nanolayer.
[0008] Preferably, the number of layers of the CrMnFeCoNi alloy nanolayer is 40 to 95 layers; the number of layers of the carbide nanolayer is 40 to 95 layers.
[0009] Preferably, the single layer thickness of the carbide nanolayer is 15 to 25 nm; the single layer thickness of the CrMnFeCoNi alloy nanolayer is 3 to 20 nm.
[0010] The present invention also provides a method for preparing the carbide-based nanocomposite film described in the above scheme, comprising the following steps:
[0011] A carbide target and a CrMnFeCoNi target are used as sputtering target materials, and alternate magnetron sputtering is performed on a substrate to obtain a carbide-based nanocomposite film on the surface of the substrate.
[0012] Preferably, the carbide target is a WC target, and the distance between the carbide target and the substrate is 60 to 80 mm; the distance between the CrMnFeCoNi target and the substrate is 60 to 80 mm.
[0013] Preferably, the CrMnFeCoNi target and the carbide target use a DC power supply; the sputtering current of the carbide target is 1.2-2.2A; the sputtering current of the CrMnFeCoNi target is 0.4-1.2A.
[0014] Preferably, the temperature of the substrate during magnetron sputtering is 200-400°C.
[0015] Preferably, the magnetron sputtering is direct current magnetron sputtering; the magnetron sputtering is performed in a protective atmosphere; the pressure of the magnetron sputtering is 0.6 to 1.2 Pa; and the bias power supply of the magnetron sputtering is -40 to -200 V.
[0016] The present invention also provides the use of the carbide-based nanocomposite film described in the above scheme or the carbide-based nanocomposite film obtained by the preparation method described in the above scheme as a protective coating.
[0017] The present invention provides a carbide-based nanocomposite film. The carbide-based nanocomposite film provided by the present invention comprises a CrMnFeCoNi alloy, wherein the content of each element in the CrMnFeCoNi alloy is the same or similar, and compared with traditional alloys, the rich elements enable the alloy to have four unique effects, including high entropy effect, lattice distortion effect, hysteresis diffusion effect and "cocktail" effect, and these unique effects enable the CrMnFeCoNi alloy to have excellent fracture toughness, and the fracture toughness thereof exceeds 200MPa√m.
[0018] The carbide-based nanocomposite film provided by the present invention adopts a nano multilayer structure, and uses a CrMnFeCoNi alloy with a different structure from that of the carbide, and periodically inserts it into the carbide to construct a nano multilayer film. There are different slip systems and significant lattice mismatches between the CrMnFeCoNi alloy nanolayer and the carbide nanolayer, which will introduce a large number of heterogeneous interfaces, which can serve as obstacles to dislocation sliding, and the layer interface can also deflect or passivate cracks, thereby simultaneously improving the hardness and fracture toughness of the material. At the same time, the CrMnFeCoNi nanolayer has a high fracture toughness and can provide toughness support; the carbide nanolayer has a high hardness and can provide mechanical support.
[0019] The nanocomposite film constructed by the present invention can combine the advantages of each nanolayer and improve the mechanical properties of the nanocomposite film through the synergistic effect of the nanolayers. Under the premise of maintaining the high strength of the carbide, the fracture toughness is significantly improved, and the wear resistance is further improved. It is a material with high hardness, high fracture toughness and high wear resistance. The hardness is above 18GPa, no cracks are generated around the micron indentation, it has a low and stable friction curve, and good friction performance.
[0020] The present invention also provides a method for preparing the carbide-based nanocomposite film described in the above scheme. The present invention periodically introduces a CrMnFeCoNi alloy nanolayer into the carbide nanolayer by magnetron sputtering technology to obtain a nanocomposite film. The carbide-based nanocomposite film provided by the present invention effectively combines the excellent fracture toughness of the CrMnFeCoNi alloy with the high hardness and high wear resistance of the carbide, and no cracks are observed around the micron indentation. At the same time, it has a low and stable friction curve and good friction performance.
[0021] The present invention also provides the use of the carbide-based nanocomposite film described in the above scheme or the carbide-based nanocomposite film obtained by the preparation method described in the above scheme as a protective coating. The carbide-based nanocomposite film provided by the present invention has high hardness, high fracture toughness and high wear resistance, significantly reduces crack failure of the material under service working conditions, can meet harsh service environments, and greatly improves the service life of materials and equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 The hardness bar graphs of the carbide-based nanocomposite films prepared in Examples 1 to 3 of the present invention and the single-layer films of Comparative Examples 1 to 2;
[0024] Figure 2 SEM images of micron indentations of the carbide-based nanocomposite films prepared in Examples 1 to 3 of the present invention and the single-layer films of Comparative Examples 1 to 2;
[0025] Figure 3 The friction coefficient curves of the carbide-based nanocomposite films prepared in Examples 1 to 3 of the present invention and the single-layer films of Comparative Examples 1 to 2 are shown;
[0026] Figure 4 The cross-sectional SEM images of the carbide-based nanocomposite films prepared in Examples 1 to 3 of the present invention;
[0027] Figure 5 This is a cross-sectional TEM image of the carbide-based nanocomposite film prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] The invention provides a carbide-based nanocomposite film, comprising alternately stacked carbide nanolayers and CrMnFeCoNi alloy nanolayers; the molar ratio of Cr, Mn, Fe, Co and Ni in the CrMnFeCoNi alloy nanolayers is 18-22:18-22:18-22:18-22:18-22.
[0029] In the present invention, the carbide nanolayer is preferably a WC nanolayer.
[0030] In the present invention, the molar ratio of Cr to Mn in the CrMnFeCoNi alloy nanolayer is preferably 18-22:18-22, specifically 18:18, 18:19, 18:20, 18:21, 18:22, 19:18, 20:18, 21:18 or 22:18.
[0031] In the present invention, the molar ratio of Cr to Fe in the CrMnFeCoNi alloy nanolayer is preferably 18-22:18-22, specifically 18:18, 18:19, 18:20, 18:21, 18:22, 19:18, 20:18, 21:18 or 22:18.
[0032] In the present invention, the molar ratio of Cr to Co in the CrMnFeCoNi alloy nanolayer is preferably 18-22:18-22, specifically 18:18, 18:19, 18:20, 18:21, 18:22, 19:18, 20:18, 21:18 or 22:18.
[0033] In the present invention, the molar ratio of Cr to Ni in the CrMnFeCoNi alloy nanolayer is preferably 18-22:18-22, specifically 18:18, 18:19, 18:20, 18:21, 18:22, 19:18, 20:18, 21:18 or 22:18.
[0034] In the present invention, the number of layers of the carbide nanolayer is preferably 40 to 95 layers, specifically 40 layers, 45 layers, 48 layers, 52 layers, 55 layers, 60 layers, 65 layers, 70 layers, 75 layers, 80 layers, 85 layers, 90 layers or 95 layers; the number of layers of the CrMnFeCoNi alloy nanolayer is preferably 40 to 95 layers, specifically 40 layers, 45 layers, 48 layers, 52 layers, 55 layers, 60 layers, 65 layers, 70 layers, 75 layers, 80 layers, 85 layers, 90 layers or 95 layers. The present invention defines a layer of WC nanolayer and a layer of CrMnFeCoNi alloy nanolayer stacked adjacently as a modulation unit.
[0035] In the present invention, the single layer thickness of the carbide nanolayer is preferably 15 to 25 nm, specifically 15 nm, 18 nm, 22 nm, 24 nm or 25 nm; the single layer thickness of the CrMnFeCoNi alloy nanolayer is preferably 3 to 20 nm, specifically 3 nm, 5 nm, 8 nm, 10 nm, 12 nm, 15 nm, 17 nm, 18 nm or 20 nm.
[0036] In the present invention, the total thickness of the carbide-based nanocomposite film is preferably 1.6 to 2.4 μm, specifically 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm or 2.4 μm.
[0037] The present invention also provides a method for preparing the carbide-based nanocomposite film described in the above scheme, comprising the following steps:
[0038] A carbide target and a CrMnFeCoNi target are used as sputtering target materials, and alternate magnetron sputtering is performed on a substrate to obtain a carbide-based nanocomposite film on the surface of the substrate.
[0039] In the present invention, the carbide target and the CrMnFeCoNi target are preferably placed on a target table respectively; the carbide target is preferably a WC target; the distance between the carbide target and the substrate is preferably 60 to 80 mm, specifically 60 mm, 65 mm, 70 mm, 75 mm or 80 mm; the distance between the CrMnFeCoNi target and the substrate is preferably 60 to 80 mm, specifically 60 mm, 65 mm, 70 mm, 75 mm or 80 mm.
[0040] In the present invention, the CrMnFeCoNi target and the carbide target preferably use a DC power supply; the sputtering current of the carbide target is preferably 1.2-2.2A, specifically 1.2A, 1.4A, 1.6A, 1.7A, 1.8A, 1.9A, 2.0A or 2.2A; the sputtering current of the CrMnFeCoNi target is preferably 0.4-1.2A, specifically 0.4A, 0.5A, 0.6A, 0.7A, 0.9A, 1.1A or 1.2A.
[0041] In a specific embodiment of the present invention, the purity of the WC target is preferably 99.999wt%, and the purity of the CrMnFeCoNi target is preferably 99.999wt%.
[0042] In the present invention, the substrate is preferably a metal substrate; the metal substrate is preferably a titanium sheet; the substrate is preferably pre-treated before use; the pre-treatment preferably includes first cleaning and drying in sequence.
[0043] In the present invention, the first cleaning preferably includes sequentially performing acetone ultrasonic cleaning and anhydrous ethanol ultrasonic cleaning; the time of the acetone ultrasonic cleaning is preferably 20 to 25 minutes, specifically 20 minutes, 22 minutes or 25 minutes; the time of the anhydrous ethanol ultrasonic cleaning is preferably 20 to 25 minutes, specifically 20 minutes, 22 minutes or 25 minutes.
[0044] In the present invention, the drying is preferably blow-drying; the gas used for the blow-drying is preferably dry nitrogen.
[0045] In the present invention, after the pre-treatment, the substrate is preferably placed on a substrate stage of a magnetron sputtering system to prepare for magnetron sputtering.
[0046] In the present invention, the magnetron sputtering is preferably DC magnetron sputtering; the magnetron sputtering equipment is preferably a magnetron sputtering system; the magnetron sputtering is preferably performed in a protective atmosphere; the protective atmosphere is preferably argon; the purity of the argon is preferably 99.995-99.999%.
[0047] In the present invention, the temperature of the substrate during magnetron sputtering is preferably 200-400°C, specifically 200°C, 240°C, 270°C, 300°C, 330°C, 360°C or 400°C.
[0048] In the present invention, the pressure of the magnetron sputtering is preferably 0.6-1.2Pa, specifically 0.6Pa, 0.8Pa, 1.0Pa or 1.2Pa.
[0049] In the present invention, the bias power supply for magnetron sputtering is preferably -40 to -200V, specifically -40V, -70V, -100V, -130V, -160V or -200V.
[0050] In a specific embodiment of the present invention, the magnetron sputtering is preferably: the sample holder is facing the carbide target for sputtering, then the sample holder is facing the CrMnFeCoNi target for sputtering, and then the sample holder is periodically rotated in the above order for sputtering.
[0051] In the present invention, the magnetron sputtering preferably further comprises a second cleaning of the substrate; the second cleaning is preferably: evacuating the magnetron sputtering system to a vacuum degree of no more than 8×10 -4 When the pressure reaches 0.04 Pa, the protective atmosphere is introduced, the ion source is turned on, and the substrate is cleaned. After cleaning, the flow rate of the protective atmosphere is adjusted to make the pressure in the magnetron sputtering system reach the target pressure.
[0052] In the present invention, the protective atmosphere is preferably argon; the purity of the argon is preferably 99.995-99.999%; the flow rate of the protective atmosphere is preferably 50-80sccm, specifically 50sccm, 60sccm, 70sccm or 80sccm.
[0053] In the present invention, the ion source voltage of the second cleaning is preferably 700-900V, specifically 700V, 750V, 800V, 850V or 900V, and the cleaning time is preferably 20-30min, specifically 20min, 22min, 25min, 27min or 30min.
[0054] In the present invention, after the magnetron sputtering, the method preferably further comprises: waiting for the temperature of the magnetron sputtering system to cool to room temperature and taking out the obtained product.
[0055] The present invention also provides the use of the carbide-based nanocomposite film described in the above scheme or the carbide-based nanocomposite film obtained by the preparation method described in the above scheme as a protective coating.
[0056] The carbide-based nanocomposite film provided by the present invention has high hardness, high fracture toughness and high wear resistance, which significantly reduces crack failure of the material under service working conditions, can meet harsh service environments, and greatly improve the service life of materials and equipment.
[0057] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0058] Example 1
[0059] This embodiment prepares a carbide-based nanocomposite film (referred to as WC / CrMnFeCoNi), comprising the following steps:
[0060] A titanium sheet was used as the substrate. Before use, the titanium sheet was cleaned in an ultrasonic cleaner with acetone and anhydrous ethanol for 25 minutes each. After cleaning, the substrate was blown dry with dry nitrogen. After drying, the substrate was placed on the substrate stage of the magnetron sputtering system to prepare for magnetron sputtering.
[0061] A WC target (purity of 99.999wt%) and a CrMnFeCoNi target (purity of 99.999wt%, molar ratio of each element of 1:1:1:1:1) were placed on the target table, respectively. The distance between the CrMnFeCoNi target and the WC target and the substrate was 70mm. The sputtering current used for the WC target was 1.8A, and the sputtering current used for the CrMnFeCoNi target was 0.4A. The vacuum degree in the magnetron sputtering system was not higher than 8×10 -4 Pa, introduce argon gas (purity of 99.999%), set the flow rate of argon gas to 80sccm, turn on the ion source, perform a second cleaning on the substrate, the ion source voltage of the second cleaning is 800V, the cleaning time is 20min, then set the temperature of the substrate to 200°C, adjust the flow rate of argon gas so that the pressure in the magnetron sputtering system is 0.8Pa, the bias power supply is -100V, and use WC target and CrMnFeCoNi target to perform alternating magnetron sputtering on the substrate, respectively, wherein the thickness of the WC nanolayer is 22nm, the thickness of the CrMnFeCoNi alloy nanolayer is 5nm, and a carbide-based nanocomposite film is obtained on the surface of the substrate with a total thickness of 2μm. After the temperature in the magnetron sputtering system is cooled to room temperature, the carbide-based nanocomposite film is taken out.
[0062] The carbide-based nanocomposite film prepared in this example was subjected to microindentation, nanoindentation and friction tests. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the hardness of the carbide-based nanocomposite film prepared in this embodiment is 23.3 GPa. Figure 2 It can be seen that no cracks were observed around the micron indentation, and the carbide-based nanocomposite film prepared in this embodiment exhibited high hardness and excellent fracture toughness. Figure 3 It can be seen that the friction curve of the carbide-based nanocomposite film prepared in this embodiment remains stable, indicating that the carbide-based nanocomposite film prepared in this embodiment has a low friction coefficient and has excellent tribological properties of low wear and resistance.
[0063] The cross section of the carbide-based nanocomposite film prepared in this embodiment was subjected to SEM testing, and the results are as follows: Figure 4 As shown. Figure 4It can be seen that the CrMnFeCoNi nanolayers and WC nanolayers are alternately deposited to form a multilayer structure, and the total thickness of the carbide-based composite film is 2 μm.
[0064] The cross section of the carbide-based nanocomposite film prepared in this example was tested by TEM. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that there are obvious alternating light and dark stripes in the figure, which confirms that the carbide-based nanocomposite film grows in layers, in which the brighter layer is the CrMnFeCoNi alloy nanolayer and the darker layer is the WC nanolayer.
[0065] Example 2
[0066] The preparation method of this embodiment is the same as that of Example 1, except that: the sputtering current used for the CrMnFeCoNi target during the preparation of this embodiment is 0.68A; in the prepared carbide-based nanocomposite film, the thickness of the WC nanolayer is 22nm, the thickness of the CrMnFeCoNi nanolayer is 10nm, and the total thickness is 2μm.
[0067] The carbide-based nanocomposite film prepared in this example was subjected to microindentation, nanoindentation and friction tests. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the hardness of the carbide-based nanocomposite film prepared in this embodiment is 21.2 GPa. Figure 2 It can be seen that no cracks were observed around the micron indentation, and the carbide-based nanocomposite film prepared in this embodiment exhibited high hardness and excellent fracture toughness. Figure 3 It can be seen that the friction curve of the carbide-based nanocomposite film prepared in this embodiment remains stable and its friction coefficient is low, which indicates that the carbide-based nanocomposite film prepared in this embodiment has excellent tribological properties of low wear and wear resistance.
[0068] The cross section of the carbide-based nanocomposite film prepared in this embodiment was subjected to SEM testing, and the results are as follows: Figure 4 As shown. Figure 4 It can be seen that the CrMnFeCoNi nanolayers and WC nanolayers are alternately deposited to form a multilayer structure, and the total thickness of the carbide-based composite film is 2 μm.
[0069] Example 3
[0070] The preparation method of this embodiment is the same as that of Example 1, except that: the sputtering current used for the CrMnFeCoNi target during the preparation of this embodiment is 1.2A; in the prepared carbide-based nanocomposite film, the thickness of the WC nanolayer is 22nm, the thickness of the CrMnFeCoNi nanolayer is 18nm, and the total thickness is 2μm.
[0071] The carbide-based nanocomposite film prepared in this example was subjected to microindentation, nanoindentation and friction tests. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the hardness of the carbide-based nanocomposite film prepared in this embodiment is 18.5 GPa. Figure 2 It can be seen that no cracks were observed around the micron indentation, and the carbide-based nanocomposite film prepared in this embodiment exhibited high hardness and excellent fracture toughness. Figure 3 It can be seen that the friction curve of the carbide-based nanocomposite film prepared in this embodiment remains stable and its friction coefficient is low, which indicates that the carbide-based nanocomposite film prepared in this embodiment has excellent tribological properties of low wear and wear resistance.
[0072] The cross section of the carbide-based nanocomposite film prepared in this embodiment was subjected to SEM testing, and the results are as follows: Figure 4 As shown. Figure 4 It can be seen that the CrMnFeCoNi nanolayers and WC nanolayers are alternately deposited to form a multilayer structure, and the total thickness of the carbide-based composite film is 2 μm.
[0073] Example 4
[0074] The preparation method of this embodiment is the same as that of embodiment 1, except that: the sputtering current used by the CrMnFeCoNi target in the preparation process of this embodiment is 0.4A, and the sputtering current used by the WC target is 1.5A; in the prepared carbide-based nanocomposite film, the thickness of the WC nanolayer is 18nm, the thickness of the CrMnFeCoNi nanolayer is 5nm, and the total thickness is 2μm. The test data of this embodiment is similar to that of embodiment 1.
[0075] Example 5
[0076] The preparation method of this embodiment is the same as that of embodiment 1, except that: the sputtering current used by the CrMnFeCoNi target in the preparation process of this embodiment is 0.68A, and the sputtering current used by the WC target is 2.1A; in the prepared carbide-based nanocomposite film, the thickness of the WC nanolayer is 25nm, the thickness of the CrMnFeCoNi nanolayer is 10nm, and the total thickness is 2μm. The test data of this embodiment is similar to that of embodiment 2.
[0077] Comparative Example 1
[0078] This comparative example prepares a CrMnFeCoNi single-layer film, comprising the following steps:
[0079] A titanium sheet was used as the substrate. Before use, the titanium sheet was cleaned in an ultrasonic cleaner with acetone and anhydrous ethanol for 25 minutes each. After cleaning, the substrate was blown dry with dry nitrogen. After drying, the substrate was placed on the substrate stage of the magnetron sputtering system to prepare for magnetron sputtering.
[0080] The CrMnFeCoNi target (purity of 99.999wt%, molar ratio of each element of 1:1:1:1:1) was placed on the target table. The distance between the CrMnFeCoNi target and the substrate was 70mm. The sputtering current used for the CrMnFeCoNi target was 1.2A. The vacuum degree in the magnetron sputtering system was not higher than 8×10 -4 Pa, introduce argon gas (purity of 99.999%), set the flow rate of argon gas to 80sccm, turn on the ion source, perform a second cleaning on the substrate, the ion source voltage of the second cleaning is 800V, the cleaning time is 20min, and then set the temperature of the substrate to 200°C, adjust the flow rate of argon gas so that the pressure in the magnetron sputtering system is 0.8Pa, the bias power supply is -100V, and magnetron sputtering is performed on the substrate with a CrMnFeCoNi target to obtain a CrMnFeCoNi single-layer film on the surface of the substrate with a total thickness of 2μm. After the temperature in the magnetron sputtering system is cooled to room temperature, the CrMnFeCoNi single-layer film is taken out.
[0081] The CrMnFeCoNi single-layer film prepared in this comparative example was subjected to microindentation, nanoindentation and friction tests. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the hardness of the CrMnFeCoNi single-layer film prepared in this comparative example is 7.3 GPa. Figure 2 It can be seen that no cracks were observed around the micron indentation. Figure 3 It can be seen from the friction curve that the friction coefficient of the CrMnFeCoNi single-layer film prepared in this comparative example is high and the friction performance is poor.
[0082] Comparative Example 2
[0083] This comparative example prepared a WC single-layer film, comprising the following steps:
[0084] A titanium sheet was used as the substrate. Before use, the titanium sheet was cleaned in an ultrasonic cleaner with acetone and anhydrous ethanol for 25 minutes each. After cleaning, the substrate was blown dry with dry nitrogen. After drying, the substrate was placed on the substrate stage of the magnetron sputtering system to prepare for magnetron sputtering.
[0085] The WC target (purity of 99.999wt%) was placed on the target table. The distance between the WC target and the substrate was 70mm. The sputtering current used by the WC target was 1.8A. The vacuum degree in the magnetron sputtering system was not higher than 8×10 -4Pa, introduce argon gas (purity of 99.999%), set the flow rate of argon gas to 80sccm, turn on the ion source, perform a second cleaning on the substrate, the ion source voltage of the second cleaning is 800V, the cleaning time is 20min, and then set the temperature of the substrate to 200°C, adjust the flow rate of argon gas so that the pressure in the magnetron sputtering system is 0.8Pa, the bias power supply is -100V, and magnetron sputtering is performed on the substrate with a WC target. A WC single-layer film with a total thickness of 2μm is obtained on the surface of the substrate. After the temperature in the magnetron sputtering system is cooled to room temperature, the WC single-layer film is taken out.
[0086] The WC single-layer film prepared in this comparative example was subjected to microindentation, nanoindentation and friction tests. The results are as follows: Figures 1 to 3 As shown. Figure 1 It can be seen that the hardness of the WC single-layer film prepared in this comparative example is 25.6 GPa. Figure 2 It can be seen that cracks appeared around the micron indentation, and its fracture toughness was poor. Figure 3 It can be seen that the WC single-layer film prepared in this comparative example has a lower friction coefficient and better friction performance.
[0087] It can be seen from the above embodiments that the carbide-based nanocomposite film provided by the present invention has high hardness, high fracture toughness and high wear resistance, with a hardness above 18 GPa, no cracks around the micron indentation, a stable friction curve, a low friction coefficient, good friction performance, and can meet harsh service environments.
[0088] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A carbide-based nanocomposite film, characterized in that: It includes carbide nanolayers and CrMnFeCoNi alloy nanolayers which are alternately stacked; The molar ratio of Cr, Mn, Fe, Co and Ni in the CrMnFeCoNi alloy nanolayer is 18-22:18-22:18-22:18-22:18-22.
2. The carbide-based nanocomposite film according to claim 1, characterized in that: The carbide nanolayer is a WC nanolayer.
3. The carbide-based nanocomposite film according to claim 1 or 2, characterized in that: The number of layers of the CrMnFeCoNi alloy nanolayer is 40 to 95; The number of the carbide nanolayers is 40 to 95.
4. The carbide-based nanocomposite film according to claim 1 or 2, characterized in that: The single layer thickness of the carbide nanolayer is 15 to 25 nm; The single layer thickness of the CrMnFeCoNi alloy nanolayer is 3-20 nm.
5. The method for preparing the carbide-based nanocomposite film according to any one of claims 1 to 4, characterized in that: The following steps are involved: A carbide target and a CrMnFeCoNi target are used as sputtering target materials, and alternate magnetron sputtering is performed on a substrate to obtain a carbide-based nanocomposite film on the surface of the substrate.
6. The preparation method according to claim 5, characterized in that: The carbide target is a WC target, and the distance between the carbide target and the substrate is 60 to 80 mm; The distance between the CrMnFeCoNi target and the substrate is 60-80 mm.
7. The preparation method according to claim 5 or 6, characterized in that: The CrMnFeCoNi target and the carbide target use a DC power supply; The sputtering current of the carbide target is 1.2 to 2.2A; The sputtering current of the CrMnFeCoNi target is 0.4-1.2A.
8. The preparation method according to claim 5, characterized in that: The temperature of the substrate during the magnetron sputtering is 200-400°C.
9. The preparation method according to claim 5 or 8, characterized in that: The magnetron sputtering is DC magnetron sputtering; The magnetron sputtering is carried out in a protective atmosphere; The pressure of the magnetron sputtering is 0.6-1.2 Pa; The bias power supply of the magnetron sputtering is -40 to -200V.
10. Use of the carbide-based nanocomposite film according to any one of claims 1 to 4 or the carbide-based nanocomposite film obtained by the preparation method according to any one of claims 5 to 9 as a protective coating.
Citation Information
Patent Citations
WC-based hard alloy material based on high-entropy alloy and preparing method of WC-based hard alloy material
CN108950343A
High-entropy alloy / WC hard layer nano multilayer film and preparation method and application thereof
CN111485209A
Optical film, sputtering target, and method for forming optical film
CN114207180A
Preparation process of CoCrFeNiWC composite coating based on addition amount of WC
CN114481124A
Photorecording medium, sputtering target and manufacturing method of photorecording medium and sputtering target
JP2008273167A